Topography and Tilt at Volcanoes - Marsden, Luke H.; Neuberg, Jürgen W.; Thomas, Mark E. (Frontiers in Earth Science, 2019)
For optimal monitoring of the deformation of a volcano, instrumentation should be deployed at the location most sensitive to changes at the suspected deformation source. The topographic effect on tilt depends strongly on the orientation of the deformation field relative to the surface on which the instrument is deployed. This fact has long been understood and corrected for in tilt measurements related to body tides and referred to as "cavity" or "topographic effects" (Harrison, 1976). Despite this, and whilst topography at volcanoes is often significant, until now the topographic effect on tilt at volcanoes has not been systematically explored. Here, we investigate the topographic effect on tilt produced by either the pressurisation of a reservoir or conduit, or shear stress as magma ascends through a conduit, using 2D axisymmetric and 3D finite element deformation modelling. We show that topography alone can amplify or reduce the tilt by more than an order of magnitude, and that the orientation of the maximum tilt is often not radial to the source. Therefore, a decrease in tilt can even be caused by an increase in deformation at the source. Hence, inverting for the source stress using simple analytical models that neglect topography could potentially lead to a misinterpretation of how the volcanic system is evolving. However, if topography is considered when deploying a tiltmeter, the topographic effect can be exploited to maximise the sensitivity of the measurement.